Pengaruh Brand Image dan Service Quality terhadap Purcahse Intention - Ilman Prasetyo (Jurnal Manajemen Bisnis dan Kewirausahaan, 2021)
The aim of this study are: First, to explore the effect of brand image on purchase intntion. Second, to explore the effect of service quality on purchase intention. The method of data collection is convenience sampling. The samples of this research are collected from 150 respondens, who are the customers of Coffee shop in Jakarta. The technique of data analysis used in this study was multiple regression analysis and classic assumption test. Testing the result of Hypoteses used the F-test, t-test, and R2. The results are: (a) the effect between brand image have a significant and positive impact toward purchase intention; (b) the effect between service quality have a significant and positive impact toward purchase intention. Tujuan dari penelitian ini adalah : pertama, untuk menguji efek dari brand image terhadap minat beli. Kedua, untuk menguji efek dari kualitas pelayanan terhadap minat beli. Metode dari pengambilan data adalah convenience sampling. Sampel merupakan pelanggan kedai kopi di Jakarta. Sampel dari penelitian ini adalah 150 responden. Teknik dari data analisis penelitian ini adalah analisis regresi berganda dan Uji asumsi klasik. Pengujian hasil hipotesis menggunakan Uji-F, Uji-t, dan R2.. Hasilnya adalah : Hasilnya adalah (a) brand image mempunyai pengaruh positif terhadap purchase intention. (b) service quality mempunyai pengaruh positif terhadap purchase intention.